Morphological, molecular and resistance responses to soft-rot disease variability among plantlets of Phalaenopsis amabilis regenerated from irradiated protocorms - Halida Adistya Putri; Agus Purwito; Sudarsono Sudarsono; Dewi Sukma (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Putri HA, Purwito A, Sudarsono, Sukma D. 2021. Morphological, molecular and resistance responses to soft-rot disease variability among plantlets of Phalaenopsis amabilis regenerated from irradiated protocorms. Biodiversitas 22: 1077-1090. Phalaenopsis amabilis (L.) Blume is a prominent donor for the white petal and sepal trait in Phalaenopsis breeding. However, it has an undesirable character, such as susceptible to soft-rot disease. Therefore, developing soft-rot resistance mutants through gamma irradiation could be explored. This study aimed to evaluate the variability of plantlets regenerated from irradiated and non-irradiated protocorms using morphology, stomatal size and molecular markers and to test responses of the plantlets against soft-rot disease. The plantlets were regenerated from irradiated (5, 10, 15 or 20 Gy) and non-irradiated protocorms. The results showed that P. amabilis plantlet variants were successfully identified based on their leaf morphology and stomatal size variations. A few plantlets have low stomatal densities, large stomatal size, and high chloroplast numbers, which indicated they were polyploids. Leaf disc assay for soft-rot disease response grouped most of the plantlets into very susceptible or susceptible. Moreover, four soft-rot resistant plantlets regenerated from irradiated and non-irradiated protocorms were successfully identified. The resistant plantlets were identified after three consecutive periods of inoculations with pathogens causing soft-rot disease. The evaluation also confirmed nucleotide variation in the Pto gene isolated from different levels of plantlet variant resistance responses.